A framework for applying ethics‐by‐design to decision support systems for emergency management. (11th June 2021) - Nussbaumer, Alexander; Pope, Andrew; Neville, Karen
Abstract: The development and utilisation of new information and communication technologies presents opportunities and risks, which bring ethical issues to the forefront. Any attempt to minimise the potential negative consequences to individuals, organisations and society resulting from the use of these technologies is challenging. In order to address these challenges, this paper presents an ethics‐by‐design approach that has been developed and implemented in the context of Decision Supports Systems for Emergency Management. Such systems help manage large and cross‐border disasters by supporting decision makers to respond on emergencies in a reasonable way by taking follow‐up actions into account. The approach taken in this paper specifically provides means to support the ethical dimensions of these decisions. Actions taken during disasters can have ramifications that persist long after a disaster has passed. The ethics‐by‐design approach presented here not only informs the design of systems, but also considers the role and training of the decision makers in the design process. The paper builds on the literature on ethics in information systems and makes a contribution to theory by providing a framework to ensure ethical considerations are embedded into the design of systems.